PENGARUH STRUKTUR SUKUK, UMUR SUKUK, DAN STATUS JAMINAN SUKUK TERHADAP PERINGKAT SUKUK PADA PERUSAHAAN YANG TERDAFTAR DI DAFTAR EFEK SYARIAH - Muzalifah, Reva; Yulia, Aida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this researchis to examine the effect of independent variables on sukuk rating of companies listed in the List of Islamic Securities in the period of 2013-2016. Independent variables that used in this researchare sukuk structure, maturity, and guarantee status. The selection ofthe sample is using apurposive samplingmethod and obtained a sample of 12 sukuk, the type of data used in this researchis secondary data such as financial statements, annual reports and statistical data of sukuk. Data collectiontechniquesusedin this researchisthe documentation. Data analysis was conductedusing thestatistical analysisthat ismultiplelinearanalysis techniques Dataprocessedby usingprogramEconometric Views(EViews) version9. The results of this study show that 52,73% dependent variable or sukuk rating can be explained by the three of independent variables. Simultaneously the three of independent variables have effect on sukuk rating. Partially, sukuk structure, maturity, and guarantee status have effect on sukuk rating.